Magnetic resonance imaging of the heart as a method of long-term monitoring of right heart function after tetralogy of Fallot surgery - Biljana Milinković; Jelena Milić; Dejan Bokonjić; Verica Prodanović; Bojan Joksimović; Siniša Ristić (Биомедицинска истраживања, 2022)
Introduction: Cardiac magnetic resonance imaging (CMR) is considered the reference diagnostic method for quantifying right ventricular size and function, and pulmonary regurgitation in patients with tetralogy of Fallot surgery. The aim of this paper is to confirm the importance of magnetic resonance continuous postoperative monitoring of right and left heart function parameters as a diagnostic method that provides the most precise and accurate assessment. Methods: The prospective observational study included subjects with TOF surgery who were diagnosed with residual morphological and/or functional disorders on control postoperative echocardiographic examinations. All subjects underwent magnetic resonance imaging of the heart on a 1.5 T scanner with dedicated coils for the heart surface according to the standard protocol for a period of one year from the beginning of the study. Criteria for exclusion from the study were: significant residual pulmonary stenosis, condition after pulmonary valve replacement, existence of residual shunt lesions, contraindications for cardiac magnetic resonance imaging (pacemaker, ICD, claustrophobia). Depending on the time elapsed since the tetralogy of Fallot surgery, the subjects were divided into groups: more than 15 years, 11−15 years, 6−10 years, less than 5 years. Results: The study included 131 subjects with an average age of 24.18 ± 11.57 years with complete correction of TOF. Intergroup differences in values of right ventricular enddiastolic volume, right ventricular ejection fraction, and left ventricular ejection fraction were demonstrated, but there was no statistically significant intergroup difference in values of pulmonary regurgitation fraction. The negative interaction of the right and left ventricles intensifies during the years of follow-up of patients after TOF surgery, which is especially true fifteen years after surgery. Conclusion: CMR has the most significant role in research efforts aimed at improving the outcomes of operated patients with tetralogy of Fallot.
Keywords: tetralogy of Fallot; right ventricular dysfunction; cardiac magnetic resonance imaging